2019
DOI: 10.1002/hed.25891
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial with axitinib in recurrent and/or metastatic salivary gland cancers of the upper aerodigestive tract

Abstract: Background Patients with prognosis recurrent/metastatic (R/M) salivary gland carcinomas (SGCs) are poor. Activity of axitinib was demonstrated in adenoid cystic carcinoma (ACC). We tested axitinib in a larger cohort of R/M SGCs including non‐ACC. Methods Axitinib was administered at 10 mg daily (dose escalation allowed) until progression or unacceptable toxicity. Null hypothesis would be rejected if more than 3 of 26 responses were observed. Results Twenty‐six patients (50% were male; 6 ACC, 20 non‐ACC) were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 28 publications
(50 reference statements)
2
27
0
1
Order By: Relevance
“…An ORR of 46.2% was reported which compares favourably with the ORR of 12-15% observed for lenvatinib as well as those reported in other TKIs trialled in R/M ACC, including axitinib [14,15], sorafenib [10][11][12][13], and sunitinib [32]. The median PFS was 19.7 months, and the median OS was not reached, both comparing favourably with lenvatinib and other TKIs [8][9][10][11][12][13][14][15][16][17][18][19]. Interestingly, patients who received a higher intensity of apatanib treatment had significantly longer PFS than those receiving a lower intensity (p = 0.024, HR 0.033, 95% CI 0.002-0.639).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…An ORR of 46.2% was reported which compares favourably with the ORR of 12-15% observed for lenvatinib as well as those reported in other TKIs trialled in R/M ACC, including axitinib [14,15], sorafenib [10][11][12][13], and sunitinib [32]. The median PFS was 19.7 months, and the median OS was not reached, both comparing favourably with lenvatinib and other TKIs [8][9][10][11][12][13][14][15][16][17][18][19]. Interestingly, patients who received a higher intensity of apatanib treatment had significantly longer PFS than those receiving a lower intensity (p = 0.024, HR 0.033, 95% CI 0.002-0.639).…”
Section: Discussionsupporting
confidence: 73%
“…The study required radiological evidence of disease progression before enrollment to evaluate the contribution of apatinib to disease stabilisation. An ORR of 46.2% was reported which compares favourably with the ORR of 12-15% observed for lenvatinib as well as those reported in other TKIs trialled in R/M ACC, including axitinib [14,15], sorafenib [10][11][12][13], and sunitinib [32]. The median PFS was 19.7 months, and the median OS was not reached, both comparing favourably with lenvatinib and other TKIs [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Other targeted therapies including axitinib, 38 tipifarnib, 259 gefitinib, 27 and lapatinib 357 have demonstrated clinical benefit rather than significant objective responses in small phase II studies, and these remain investigational. Recommendation 6.6.…”
Section: Clinicalmentioning
confidence: 99%
“…For VEGFR, it was found that there was an association with recurrence and metastases [47]. Medication tested in phase II trials included dovitinib (FGFR, VEGFR, PDGFR, c-Kit) [48,49], sunitinib (VEGFR, c-Kit, PDGFR) [50], regorafenib (VEGRF, FGFR, PDGFR) [51], nintedanib (VEGFR, FGFR, PDGFR) [52], lenvatinib (VEGFR, FGFR, PDGFR) [53,54], axitinib (VEGFR, PDGFR, c-Kit) [55,56], and sorafenib (VEGFR, PDGFR, c-Kit) [62,76]. For sunitinib, regorafenib, and nintedanib, no overall response rates could be seen.…”
Section: Vegfrmentioning
confidence: 99%